The role of the cilium in hereditary tumor predisposition syndromes - Klasson, Timothy D.; Giles, Rachel H. (Journal of Pediatric Genetics, 2014)
The primary cilium is a highly conserved cell organelle that is closely connected to processes involved in cell patterning and replication. Amongst their many functions, cilia act as “signal towers” through which cell-cell signaling cascades pass. Dysfunction of cilia or the myriad processes that are connected with cilium function can lead to disease. Due to the sheer number of cellular processes that at some point involve the primary cilium, the effects of misregulation are highly heterogeneous between different cell populations. However, because of the importance of primary cilia in the development, growth, patterning and orientation of cells and tissues, a common thread has emerged in which defective cilia can lead to disorganization, which can contribute to the growth of neoplasms, including cancer and pre-cancerous phenotypes. Because cilia are so vital for signaling during cell replication and the cell fate decisions that are important in childhood growth, symptoms often arise early in life. Here we review recent work connecting misregulation of the primary cilium with tumor formation in a variety of tissues in the developing body, with a particular focus on the syndromes in which classic tumor genes are mutated, including von Hippel-Lindau disease (OMIM 193300), adenomatous polyposis coli (OMIM 175100), tuberous sclerosis (OMIM 191100) and Birt-Hogg-Dubé syndrome (OMIM 135150). Timely diagnosis of these syndromes is essential for entry into appropriate screening protocols, which have been shown to effectively prolong life expectancy in these cohorts of patients.
Keywords: Cilia; von Hippel-Lindau disease; cyst; renal cell carcinoma; medulloblastoma